THE HEDGING OF MAXIMS BY DAVID BECKHAM IN GOOGLE+ INTERVIEW - AYUNINGSIH, IKA KUSTI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Ayuningsih, Ika Kusti. 2014. The Hedging of Maxims by David Beckham in Google+ Interview. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas  Brawijaya.Supervisor: Iis Nur Rodliyah; Co-supervisor: Agus GozaliKeywords: Pragmatics, Cooperative Principle, Maxim, Hedging, Google+ Interview Communication is the process of exchanging information. In conversation, speakers sometimes use particular words or phrases to mitigate their statements and to indicate uncertainty in their utterances. The using of those particular words and phrases are known as hedging. In linguistics, the sub field studying contextual meaning in conversation and hedging is pragmatics. This study aims to answer two problems, which are (1) to find out the types of the hedging of maxims used by David Beckham in Google+ Interview and (2) to find out the contexts that cause the occurance of the hedging of maxims applied by David Beckham in Google+ Interview.This research is a descriptive qualitative because this research focuses ondescribing the data about what types of hedging maxim produced by DavidBeckham in Google+ interview held in January 2012. The writer also analyzes thecontexts of using hedging maxim found in David Beckham’s utterances. In thisresearch, the writer uses Hymes’s  SPEAKING theory (1974) to analyze the data.This research reveals that David Beckham hedged maxim of quality, maxim of quantity and maxim of manner in his utterances. The writer found 37 utterances which consist of the hedging of maxims. There are 31 hedging maxim of quality, 5 hedging maxim of quantity and 1 hedging maxim of manner. The SPEAKING features theory is used by the writer to help analyze the contexts that cause the occurance of the hedging of maxims by David Beckham in Google+ Interview.The writer suggests that the next researcher analyze different objects from this research and also use different theories of the hedging of maxims from the ones used in this research.